Did the extended coverage policy contribute to alleviating socioeconomic inequality in untreated dental caries of both children and adolescents in South Korea? - Bo-Mi Shin; Se-Hwan Jung; Myoung-Hee Kim; Jae-In Ryu (BMC, 2020)
Abstract Background Dental sealants have been covered by the National Health Insurance Service (NHIS) since December 2009 in South Korea. This study aims to determine whether the socioeconomic inequality in untreated dental caries decreased after implementing the extended coverage policy for dental sealant. Methods The data were derived from the fourth (2007-2009) and sixth (2013-2015) waves of the Korean National Health and Nutrition Examination Survey (KNHANES) conducted by the Korea Centers for Disease Control and Prevention (KCDC). Dental caries and sealant experience by income quartiles were tested using the Rao-Scott chi-squared test. In order to examine socioeconomic inequalities and their trends over time, the prevalence ratios (PRs), slope index of inequality (SII), and relative index of inequality (RII) were estimated for each wave and age group. All analyses were conducted using SAS version 9.3. Results The adjusted PRs of untreated dental caries and sealants in the poorest in the aged 6-11 group were significantly higher and lower, respectively, compared to the most affluent quartile group for the fourth wave; however, all significant differences disappeared for the sixth wave, after the sealant coverage. The gap between the lowest and the highest was similar for the aged 12-18 group but it widened in the untreated dental caries even after the sealant coverage. The statistical significance of the PRs was maintained at the sixth wave for both caries and sealants. Children showed decreases in both SII and RII over time so its significance disappeared. The SII among adolescents decreased over time but the RII of untreated dental caries increased. Conclusions This study found that the NHIS coverage expansion of dental care had a positive effect on overall status in dental health among children and adolescents. However, younger children benefited more in terms of inequalities. Our findings indicate that strategies to enhance access to preventive dental services should consider the differential effects for the vulnerable population in terms of socioeconomic status and age from the beginning stage of the policy.